The color change in polychromatic organic light-emitting field-effect transistors: Optical filtering versus reemission - Melzer, Christian; Seggern, Heinz von (Organic electronics, 2014)
In this contribution the color conversion process of a polychromatic organic light-emitting field-effect transistor (OLET) is revisited on the basis of an analytic device model. The device of interest consists of a color conversion layer out of rubrene on top of a monochromatic light-emitting transistor based on poly(9,9-di-n-octyl-fluorene-alt-benzothiadiazole) (F8BT). The model describes the relation of color coordinate and emission intensity - set by the applied drain and gate biases - linking the optoelectronic response of the employed monochromatic OLET to the optical processes occurring in the color conversion layer. The model shows that the color shift is rather due to partial absorption of the F8BT emission by rubrene than, as was claimed earlier, due to a color conversion process by absorption and reemission in the conversion layer. In addition to the earlier publication, it will be demonstrated that such a device allows for an independent electrical tunability of emission intensity and color coordinate within the color span of the F8BT and the rubrene spectrum being a unique feature of such a polychromatic light-emitting field-effect transistor.
Gesehen am 09.07.2020